Percutaneous edge‐to‐edge repair of severe mitral regurgitation using the MitraClip XTR versus NTR system. Issue 5 (24th March 2021) - Doldi, Philipp M.; Brinkmann, Isabel; Orban, Mathias; Stolz, Lukas; Orban, Martin; Stocker, Thomas; Loew, Kornelia; Buech, Joscha; Nabauer, Michael; Illigens, Ben; Cerqueira, Tiago Lemos; Siepmann, Timo; et al.
Abstract: Background: Transcatheter mitral valve repair (TMVR) has shown to improve symptoms and functional capacity in patients with severe mitral valve regurgitation (MR). Novel device developments provide the technology to treat patients with complex anatomies and large coaptation gaps. Nevertheless, the question of superiority of one device remains unanswered. We aimed to compare the MitraClip XTR and MitraClip NTR system in a real world setting. Hypothesis: TMVR with the MitraClip XTR system is equally effective, but associated with a higher risk of leaflet injury. Methods: We retrospectively analyzed peri‐procedural and mid‐term clinical and echocardiographic outcomes of 113 patients treated for severe MR between March 2018 and August 2019 at the University Hospital of Munich. Results: Postprocedural MR reduction to ≤2+ was comparable in both groups (XTR: 96.1% vs. NTR: 97.6%, p =  .38). There was a significant difference in a composite safety endpoint of periprocedural Major adverse cardiac and cerebrovascular events (MACCE) including leaflet injury between groups (XTR 14.6% vs. NTR 1.7%, 95% CI [2.7, 24.6], p =  .012). After a median follow‐up of 8.5 (4.4, 14.0) months, durable reduction of MR was confirmed (XTR: in 91.9% vs. NTR: 96.8%, p =  .31) and clinical and symptomatic improvement was comparable in both groups accordingly. Conclusion: While efficacy was comparable in both treatment groups, patients treated with the MitraClip XTR systems showed more events of acute leaflet tear and single leaflet device attachment (SLDA). A detailed echocardiographic assessment should be done to identify risk candidates for acute leaflet injury.